Effectiveness of Short-Term Health Coaching on Diabetes Control and Self-Management Efficacy: A Quasi-Experimental Trial - Chen, Ruey-Yu; Huang, Li-Chi; Su, Chien-Tien; Chang, Yao-Tsung; Chu, Chia-Lin; Chang, Chiao-Ling; Lin, Ching-Ling (Frontiers in Public Health, 2019)
Introduction: The aim of this study was to explore the effectiveness in HbA1c lowering and self-efficacy of diabetes self-management of a 6 months coaching intervention. Methods: This paper was a two-armed coaching intervention study in which 116 participants who presented type 2 diabetes were recruited at a medical center. The intervention group had health coaching and usual care for 6 months, whereas the control had usual care only. The main outcome variables were HbA1c level and self-efficacy of diabetes self-management, in followed-up measure at 3 and 6 months. Results: We found that an approximate 0.68% (CI = 0.40 to 0.96) reduction in HbA1c was achieved after a 6-month health coaching. Both physical activity and self-efficacy of diabetes self-management were shown to benefit by health coaching. Conclusions: Health coaching might be an effective strategy to enhance self-management for diabetes patients in Taiwan where “Diabetes Shared Care Network” had been implemented for over 20 years. Consider limitations of this study, more studies with designs that yield higher quality evidence for the role of health coaching in diabetic patients are needed. Clinical Trial Registration:www.isrctn.com (ID number: ISRCTN52454940, date: 10 May, 2018, retrospectively registered).